Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine - Lockey, David; Bache, Kristi; Lossius, Hans Morten
Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine (SJTREM) encompasses all aspects of the epidemiology, etiology, pathophysiology, diagnosis, treatment, rehabilitation and  prevention of acute illnesses and trauma, resuscitation and emergency medicine, with particular interest in the multidisciplinary aspects of the chain of survival. Contributions focusing on education, training, implementation, as well as ethical and socio-economic aspects of trauma management are welcome.